Coronary Microvascular Dysfunction: Epidemiology, Clinical Presentation, Diagnosis and Treatment - E. L. Trisvetova (Рациональная фармакотерапия в кардиологии)
In a significant number of patients with symptoms of angina pectoris or myocardial infarction with ischemic changes in the myocardium, according to the results of instrumental research methods, there is no hemodynamically significant stenosis of the coronary arteries. In these cases, vasospastic angina or microvascular dysfunction is considered the cause of coronary heart disease. Coronary microvascular dysfunction is caused by several pathological mechanisms that cause structural and functional disorders in the microvascular bed of the heart. Clinical groups of coronary microvascular dysfunction include angina pectoris and myocardial ischemia without obstructive coronary artery disease (primary coronary microvascular dysfunction), in combination with coronary atherosclerosis, with myocardial damage and iatrogenic nature. Diagnostics of microvascular disorders is carried out on the basis of the results of non-invasive and invasive methods, which make it possible to clarify the nature of the changes and choose an effective nondrug and drug treatment. The prognosis for coronary microvascular dysfunction is poor, due to the development of cardiovascular complications and death, a high risk of disability, and a decrease in the quality of life of patients.